3 Single shot stereotactic body radiotherapy for localized prostate cancer: Case report. (December 2018) - Koutsouvelis, N.; Dipasquale, G.; Dubouloz, A.; Jaccard, M.; Miralbell, R.; Zilli, T.
Abstract : Introduction: We report on the quality assurance (QA) and treatment management of the first patient included in the ONE SHOT trial. ONE SHOT, single shot stereotactic body radiotherapy (SBRT) for localized prostate cancer, is a multicenter single arm phase I/II trial which will enrolled 45 patients in total. Its main objective is to determine the safety and efficacy of a single SBRT fraction at a dose of 19 Gy in patients with localized prostate cancer. Indeed, recent data showed good tolerance and biochemical control after single interstitial application of 19/20 Gy to the prostate or after SBRT in five fractions, so that ultra-hypofractionated single-dose SBRT employing imaged-guided radiotherapy and real-time tumour tracking with implanted electromagnetic transponders (Calypso® with DynamicEdge™ gating) may be feasible with a safe toxicity profile and an optimal long-term tumor control. Methods: Three Calypso beacons were implanted in the patient prostate 4 days before the planning CT scan. The patient was imaged with empty rectum and full bladder with 1 mm slices thickness. For urethra contouring and visualization during treatment, a non-radiopaque catheter was inserted during CT simulation and before the treatment delivery. The prescription dose was 19 Gy in a single fraction to the whole prostate gland ±proximal seminal vesicles and 17 Gy to the urethra planning-risk volume (PRV). The plan consisted into 2 full VMAT arcs using 10MV FFF beam from the TrueBeam linac with 6 degrees of freedom couch. It was optimized on Eclipse TPS (Varian) with Rapidplan™, a knowledge-based planning software, and the dose was calculated with AAA v13026 algorithm. QA controls included portal dosimetry (PD) (Varian, PDIP v13026), absolute dose measurements with Diamond detector (PTW) inserted in Lucy 3D QA phantom (Standard Imaging) and Gafchromic film measurements (EBT-XD films). Results: The treatment plan of the first ONE SHOT patient satisfied the dose-volume constraints for all OARs and the coverage requirement for the PTV and PRV. The total number of monitor units for the two arcs was 7125. The results of the PD QA were within the tolerance, with Gamma index 1%/1 mm  = 98.7%. For absolute dose measurement, the difference between expected and measured dose was 1.7% inside PRV and 3% in the PTV region. Film gamma index with 4%/1 mm criteria was 97.4%. Patient positioning before treatment required two cone-beam CT (CBCT) before the first arc, because Calypso detected a 2 mm shift in the longitudinal direction after the couch adjustment made after the 1st CBCT. The first arc was treated without interruption and a third CBCT was acquired between the arcs. However, no shift was observed and the second arc was treated without patient realignment. Conclusions: QA results were all within the tolerance for SBRT treatment and the first ONE SHOT patient was treated successfully as planned.